2016
DOI: 10.1111/bph.13472
|View full text |Cite
|
Sign up to set email alerts
|

The pregnane X receptor down‐regulates organic cation transporter 1 (SLC22A1) in human hepatocytes by competing for (“squelching”) SRC‐1 coactivator

Abstract: BACKGROUND AND PURPOSEThe organic cation transporter 1 (OCT1) transports cationic drugs into hepatocytes. The high hepatic expression of OCT1 is controlled by the HNF4α and USF transcription factors. Pregnane X receptor (PXR) mediates induction of the principal xenobiotic metabolizing enzymes and transporters in the liver. Here, we have assessed the down-regulation of OCT1 expression by PXR activation. EXPERIMENTAL APPROACHWe used primary human hepatocytes and related cell lines to measure OCT1 expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…Therefore, a functional cross-talk between PXR and HNF-4α, a key hepatic regulator of genes involved in bile acid synthesis including the cholesterol 7-alpha hydroxylase (CYP7A1) and sterol 12-alpha hydroxylase (CYP8B1) genes, has been studied. It was shown that PXR interacts with the coactivator PGC-1α through its C-terminal ligand binding domain in a rifampicin-dependent manner and that PGC-1α coactivates PXR transactivation (Bhalla et al, 2004;Chiang, 2005, 2006;Hyrsova et al, 2016). Consistently, endogenous Pgc-1α from mouse liver extracts was found to bind to PXR, and recombinant PGC-1α directly interacts with PXR.…”
Section: Pgc-1αmentioning
confidence: 89%
See 4 more Smart Citations
“…Therefore, a functional cross-talk between PXR and HNF-4α, a key hepatic regulator of genes involved in bile acid synthesis including the cholesterol 7-alpha hydroxylase (CYP7A1) and sterol 12-alpha hydroxylase (CYP8B1) genes, has been studied. It was shown that PXR interacts with the coactivator PGC-1α through its C-terminal ligand binding domain in a rifampicin-dependent manner and that PGC-1α coactivates PXR transactivation (Bhalla et al, 2004;Chiang, 2005, 2006;Hyrsova et al, 2016). Consistently, endogenous Pgc-1α from mouse liver extracts was found to bind to PXR, and recombinant PGC-1α directly interacts with PXR.…”
Section: Pgc-1αmentioning
confidence: 89%
“…PGC-1α at the same time coactivates and enhances the transcriptional activity of HNF-4α in the regulation of several liver-specific genes, including CYP7A1, CYP8A1, SHP, OCT1 (SLC22A1), and PEPCK1 (Bhalla et al, 2004;Chiang, 2005, 2006;Hyrsova et al, 2016). This PGC-1α coactivation of HNF4α was reported to be suppressed by PXR ligands in an SHP-independent manner.…”
Section: Pgc-1αmentioning
confidence: 95%
See 3 more Smart Citations